Pengaruh Kualitas Pelayanan Guest Relation Officer Terhadap Kepuasan Tamu di Hotel JW Marriott Surabaya - Febrian Yunila; Kris Cahyani Ermawati; Titik Akiriningsih (Jurnal Pariwisata Indonesia, 2021)
This research is about the service quality of guest relation officers at JW Marriott Hotel Surabaya. This study aims to determine the quality of service provided to guests and its effect on guest satisfaction at the JW Marriott Surabaya hotel. This research is presented in a qualitative descriptive manner with primary and secondary data sources, this study uses data collection techniques through interviews, observation, documentation, and literature study. The total population is 10 front office department staff, and the sample is 4 staff guest relations officers. This study aims to determine the problems and desires of guests at the JW Marriott Hotel Surabaya. The result that can be taken is that the quality of service provided by the Guest Relations Officer at the JW Marriott Hotel Surabaya to guests is very good and according to the procedure so that it can effectively affect the level of guest satisfaction, with the conclusion that good service is carried out so that guest satisfaction can be met.